Nosema bombi (Microsporidia: Nosematidae) and trypanosomatid prevalence in spring bumble bee queens (Hymenoptera: Apidae: Bombus) in Kansas - Tripodi, Amber D.; Cibils-Stewart, Ximena; McCornack, Brian P.; Szalanski, Allen L. (My University, 2014)
Several species of bumble bees are declining in the United States; these declining populations often show higher prevalence of Nosema bombi, a microsporidian pathogen. To date, surveys of bumble bee pathogens in the United States have only been conducted on workers and males, yet the health of a population is ultimately dependent on the success of colony-founding queens. We conducted a molecular-diagnostic survey of the prevalence of N. bombi and trypanosomatids, such as Crithidia bombi, in six species of spring queens (n  =  142) collected in 2011 and 2013 at three sites in central Kansas. Nosema bombi was found in 27% of Bombus pensylvanicus and 13% of B. auricomus but was not found in the other species sampled. Trypanosomatids were only found in B. pensylvanicus (9%) during the May 2013 sampling period. The high prevalence of N. bombi in B. pensylvanicus is consistent with other surveys for this pathogen in other castes, but the high prevalence of N. bombi in B. auricomus is a novel finding. Although the conservation status of B. auricomus has not been thoroughly assessed, two recently published surveys showed that B. auricomus were less common in portions of the species' range. Based on those findings and an oft-cited link between N. bombi prevalence and bumble bee species' decline (e.g., B. pensylvanicus) in other studies, our findings suggest B. auricomus populations in Kansas may warrant further scrutiny.
Citation: Tribodi, A., Cibils-Stewart, X., McCornack, B., & Szlanski, A. (2014). Nosema bombi (Microsporidia: Nosematidae) and Trypanosomatid Prevalence in Spring Bumble Bee Queens (Hymenoptera: Apidae: Bombus) in Kansas. Journal of the Entomological Society, 87(2), 225-233. https://doi.org/10.2317/JKES130730.1
Keywords: Bombus; Bumble bee; Spring queen; Nosema bombi; Crithidia bombi; Kansas